Biotic and abiotic drivers of species loss rate in isolated lakes. Issue 6 (18th April 2019) - Bellard, Céline; Englund, Göran; Hugueny, Bernard
Abstract: Today, anthropogenic impacts are causing a serious crisis for global biodiversity, with rates of extinction increasing at an unprecedented rate. Extinctions typically occur after a certain delay, and understanding the mechanisms causing delays is a key challenge for both fundamental and applied perspectives. Here, we make use of natural experiments, the isolation of lakes by land uplift in Northern Scandinavia, to examine how yearly extinction rates are affected by time since isolation and a range of abiotic and biotic factors. In this aim, we adapted a model of delayed species loss within isolated communities to test the effects of time since isolation, area, pH, depth and the presence/absence of piscivores on extinction rates. As expected, we found that small and/or young lakes experience a higher annual rate of extinctions per species than larger and/or older ones. Compared to previous studies that were conducted for either young (few thousand years ago) or very old (>10, 000 years ago) isolates, we demonstrated over a large and continuous temporal scales (50–5, 000 years), similar relationship between extinction rates and age. We also show that extinction rates are modified by local environmental factors such as a strong negative effect of increasing pH. Our results urge for the need to consider the time since critical environmental changes occurred when studying extinction rates. In a wider perspective, our study demonstrates the need to consider extinction debts when modelling future effects of climate change, land‐use changes or biological invasions on biodiversity. Abstract : Today, anthropogenic impacts are causing a serious crisis for global biodiversity, with rates of extinction increasing at an unprecedented rate. Extinctions typically occur after a certain delay, and understanding the mechanisms causing delays is a key challenge for both fundamental and applied perspectives. Here, the authors make use of natural experiments, the isolation of lakes by land uplift in Northern Scandinavia, to examine how yearly extinction rates are affected by time since isolation and a range of abiotic and biotic factors.